Universal adhesive: the effect of different simulated pulpal pressure fluids and bonding modes to dentin - Gonçalves, Lucélia Lemes; Da Silva, Tânia Mara; Prakki, Anuradha; Barcellos, Daphne Camara; Caneppele, Taciana Marco Ferraz [UNESP]; De Oliveira, Hueder Paulo Moisés; Gonçalves, Sérgio Eduardo de Paiva [UNESP] (Springer Nature, 2022)
The aim of this study was to evaluate the effect of SPP with either fetal bovine serum (FBS) or deionized water (DW) on the bond strength (μTBS) of a Universal adhesive to dentin, in both etch-and-rinse (ER) and self-etch (SE) modes. The kinematic viscosity (cSt) of FBS and DW was measured at 25 °C ± 0.1 ºC. Seventy-two sound human molars were sectioned and randomly divided into three groups according to the SPP conditions: (1) Control (0 cm H2O), (2) SPP (15 cm H2O) with FBS, (3) SPP (15 cm H2O) with DW. Each group was subdivided (n = 10) based on the bonding modes: ER (37% phosphoric acid + ScothBond Universal Adhesive) or SE (ScothBond Universal Adhesive). Samples were then submitted to μTBS. Data were analyzed by Student’s t test, two-way ANOVA and Tukey tests (p < 0.05). The cSt results showed that DW (23.59 ± 0.39) had significantly higher values than FBS (22.33 ± 0.06). With regard to SPP, the control group (36.1 MPa) had significantly higher values of μTBS when compared to the SPP using FBS (31.06 MPa) and SPP with DW (26.55 MPa). According to ANOVA, the bonding modes and the interaction of simulated pulpal pressure (SPP) did not statistically influence the results (p < 0.05). The presence of SPP reduced the bond strength of Universal adhesive to dentin. DW during SPP had significantly reduced bonding values when compared to FBS. Bonding strategies were not affected by SPP when evaluated in a short period of time (24 h).
Keywords: Adhesives; Dental bonding; Dental pulp